PENENTUAN KANDUNGAN LOGAM ESENSIAL (Fe, Zn DAN Cu) DALAM DAUN SIRIH MERAH (Piper crocatum) SEGAR, AIR REBUSAN DAN AIR SEDUHANNYA DENGAN METODE SPEKTROSKOPI SERAPAN ATOM(SSA) - Indrawati -; Willsant Saputra; Refilda - (Universitas Andalas, 2014)
Vol 7 No 2ABSTRACTDetermination of essential metals (Fe, Zn and Cu) in red betel leaf has been carried out by usingAtomic Absorption Spectrophotometer (AAS). Fresh and dry red betel leaf extracted in 75 mLby boiled and brewed distilled water for 5, 10, 15 and 20 minutes. In the fresh red betel leafmetal content (Fe, Zn and Cu) were 0,3257 %, 0,173 % and 0,0278 % and the highest metalcontent (Fe, Zn and Cu) found in dry red betel leaf which were boiled for 20 minutes with theconcentration 0,0539 %, 0,0305 % and 0,0128 %. Red betel leaf is a source of essential metalsneeded by the body.Keywords: Atomic Absorption Spectrophotometry (AAS), Red betel leaf (Piper crocatum),decoction water, steeping water, Fe, Zn and Cu